Who Matters Most? Rethinking Stakeholder Priorities in Nickel Mining Companies Central Sulawesi - Ayu Sagita, Virginia; Dwi Abadi, Medi Trilaksono; Rahmawati, Keny; Wisnu Lusantono, Oktarian; Hervianto, Arif (Jurnal Paradigma, 2025)
Community empowerment and development (PPM) is the focus of this study, which examines the nickel mining business in Central Sulawesi, Indonesia. The primary objective of the study is to identify, prioritize, and engage with internal and external stakeholders. Everyone from affected communities to non-profits and even city councils might be considered a stakeholder. It makes use of the Power-Interest Matrix and Freeman's theory of stakeholders. It becomes more difficult to maintain social, economic, and environmental stability as more enterprises relocate to areas with abundant resources. The interplay between stakeholders was investigated in this qualitative study via the use of tools such as social mapping, in-depth interviews, focus groups, field observations, and community involvement forums. Stakeholders' objectives shift with time in response to environmental, social, and political variables, according to the findings. Every one of the matrix's four corners considers the actions and worries of the most influential parties. The findings highlight the significance of adaptive approaches, transparent supervision, and site-specific planning in the success of PPM. Infrastructure, economic resilience, health, and education are just a few sectors that can benefit from hearing from those who will really be using a program. More resources can be used, more people can accept them, and organizations can stay in business longer with the help of stakeholder power mapping. By enhancing the CSR approach with spatial data and participative models, this work improves stakeholder theory. This provides extractive companies with procedures that can be used by many different persons and can be reused.